2014
DOI: 10.5301/jva.5000281
|View full text |Cite
|
Sign up to set email alerts
|

The Intracavitary ECG Method for Positioning the Tip of Central Venous access Devices in Pediatric Patients: Results of an Italian Multicenter Study

Abstract: We conclude that the IC-ECG method is safe and accurate in the pediatric patients. The applicability of the method is 99.4% and its feasibility is 99.4%. The accuracy is 95.8% and even higher (98.8%) when using a dedicated ECG monitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
86
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 22 publications
3
86
0
4
Order By: Relevance
“…The current findings indicate that this alterative technique could be as accurate as radiological methods as well as safe, while providing real-time monitoring and less need for X-ray confirmation [1, 13]. In a recent prospective, non-controlled Italian study, Rossetti et al reported that IC ECG was up to 95.8% as effective as X-ray [14]. However, there is a lack of randomized controlled studies comparing these two methods properly.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…The current findings indicate that this alterative technique could be as accurate as radiological methods as well as safe, while providing real-time monitoring and less need for X-ray confirmation [1, 13]. In a recent prospective, non-controlled Italian study, Rossetti et al reported that IC ECG was up to 95.8% as effective as X-ray [14]. However, there is a lack of randomized controlled studies comparing these two methods properly.…”
Section: Introductionmentioning
confidence: 86%
“…Most recommendations from the USA [8–10] propose that the tip should be placed in the lower third of the superior vena cava (SVC), while European guidelines [11, 12] often regard the upper part of the atrium as acceptable. Specifically, Pittiruti et al [13, 14] agreed that for chemotherapy, the tip should preferably be placed in the lower third of the SVC. Chinese nursing practice standards require that the catheter tip be placed in the SVC [15].…”
Section: Introductionmentioning
confidence: 99%
“…), что коррелирует с литературными данны-ми [1,4,5]. Установленный факт свидетельствует о необходимости применения интраоперационной рентгеноскопии, однако результаты, полученные некоторыми авторами, позволяют рассматривать установку ЦКПВ под мониторингом интраопераци-онной электрокардиограммы (ЭКГ) [6][7][8]. На наш взгляд, ЭКГ-контроль с применением современных навигационных систем, например Bard Sherlock (Bard Access Systems, Inc., США), может служить альтернативой установке с использованием ана-томических ориентиров.…”
Section: оригинальные статьиunclassified
“…Данной тактики придерживаются и другие специалисты [4][5][6]. При этом некоторые авторы рекомендуют выполнять установку ЦКПВ и ИВПС у взрослых пациентов с использованием интраоперационной электро-кардиографии [7][8][9]. Поскольку у детей необходимо минимизировать время, затрачиваемое на манипу-ляцию, интраоперационная рентгеноскопия являет-ся предпочтительным методом.…”
Section: нежелательные явленияunclassified